Chronic Exposure to Community Violence and Criminal Behavior: A Marginal Structural Modeling Approach - Petrich, Damon M. (Journal of quantitative criminology, 2024)
ObjectivesAssess the hypothesis that the effects of community violence on delinquency accumulate as exposures increase in chronicity over time. Few existing studies have examined this hypothesis, and none have accounted for the possibility of time-variant confounding.MethodsThe sample comprised seven years of prospective, longitudinal data on 986 juvenile offenders from the Pathways to Desistance study. Inverse probability of treatment-weighted marginal structural models were used to account for time-variant confounders that influence selection into victimization and witnessing violence across the first six years of the study. Outcomes (any, aggressive, and income offending) were assessed in the seventh year.ResultsAnalyses illustrate that failing to account for time-variant confounding—or doing so with traditional regression methods—substantially biases effect estimates. Properly specified marginal structural models show that each additional year with at least one victimization event increased the probabilities of participants’ offending during the seventh year of the study by 4.0–5.5 percentage points, whereas witnessing violence increased these probabilities by 2.9–3.7 percentage points.ConclusionsThe study shows that chronic exposure to community violence poses a substantial threat to development, including the cessation of crime by justice-involved adolescents and emerging adults. More work is needed, however, to understand the intervening mechanisms involved. Implications for policies to reduce community violence and for analyses of other time-varying exposures are discussed.